Synergistic coupling of anammox and mixotrophic sulfide-driven denitrification for extensive nitrogen removal - Yifan Zhang; Matthew J. Rogers; Guofang Xu; Kun-Lin Yang; Jianzhong He (ENGINEERING Environment, 2026)

Rapid minimally invasive subsurface archaeological site prospection on Roti Island, Indonesia - Kasih Norman; Kelsey Lowe; Matthew Forbes; Thomas Sutikna; Anton Ferdianto; Rachel Wood; Stewart J. Fallon; Rebecca Esmay; Jatmiko; I Putu Yuda Haribuana; I Made Agus Julianto; Ashleigh J. Rogers; et al. (Quaternary International, 2026)

Operationalising resilience-based management at scale: A meta-adaptive blueprint from the Great Barrier Reef crown-of-thorns starfish control program - Samuel A. Matthews; Michael Bode; Roger Beeden; Mary C. Bonin; Cameron S. Fletcher; Brigid Kerrigan; Isobel Ryan; Jennifer Wilmes; Alice White; David H. Williamson (Biological Conservation, 2026)

A multi-stage framework for validating targeted environmental DNA (eDNA) assays: from in silico design to in vitro and in situ testing for fisheries monitoring - Matthew R. Charron; Brooklynne M. L. Keber; Rina Guxholli; Steven Rogers; Jessie L. Ogden; Paige W. Breault; Arfa A. Khan; Robert H. Hanner; Daniel D. Heath; Scott A. Pavey; Margaret F. Docker (Environmental Biology of Fishes, 2026)

Microclimate and environmental change decades following repeat wildfire and vegetation type conversion in a central Arizona ponderosa pine forest - Matthew D. Petrie; Keegan D. Hammond; Joel A. Biederman; Charles J. Devine; Jackson M. Leonard; Roger Tyler (Agricultural and Forest Meteorology, 2026)

Concurrent Phosphite Oxidation and Adenosine Phosphorylation Under Prebiotic Evaporative Conditions - Maheen Gull; Judit E. Šponer; Harold A. Cruz; Edoardo J. Gallazi; Benjamin Smith; Scott A. McCallum; Karyn L. Rogers; Matthew A. Pasek (Journal of Molecular Evolution, 2026)

Derivation and evaluation of Landsat-derived annual aboveground biomass maps for Arctic and Boreal North America, 1984-2022 - Wanwan Liang; Olivier van Lier; Mark A. Friedl; James T. Randerson; Brendan M. Rogers; Arden Burrell; Kai-Ting Hu; Piotr Tompalski; Matthew J. Macander; Daryl Yang; Douglas C. Morton; Eric Bullock; et al. (Remote Sensing of Environment, 2026)

Diet composition has a greater effect on larval and juvenile polar cod (Boreogadus saida) growth rates than temperature in a warming Pacific Arctic - Esther D. Goldstein; Kelia E. Axler; Jesse F. Lamb; Matthew C. Rogers; Janet T. Duffy-Anderson (Continental Shelf Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Mangrove sediments reveal drivers of Late Holocene sea-level change in the equatorial Pacific Ocean - Juliet P. Sefton; Andrew C. Kemp; Simon E. Engelhart; Matthew J. Brain; Joanna C. Ellison; Roger Creel; Christopher G. Piecuch; Robert E. Kopp; Blair Charley; Saimon Lihpai (Quaternary Science Reviews, 2026)

Vanadium concentrations and speciation across the chemocline of a euxinic estuary. 1: geochemical cycling and fixation in euxinic sediments - Anant Misra; Omolola A. Akintomide; Jaxon Dii Horne; Segun Adebayo; Roger P. Kelly; Susan A. Welch; Matthew I. Leybourne; Christopher D. White; Karen H. Johannesson (Geochimica et Cosmochimica Acta, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Isotopic composition of individual hydrobiidae gastropods from neotropical lakes Esmeralda and Chichancanab in the Maya Cochuah region, Mexico: implications for palaeolimnological research - Haydar B. Martinez-Dyrzo; Matthew D. Jones; Sarah E. Metcalfe; Melanie J. Leng; Roger Medina-Gonzalez (Journal of Paleolimnology, 2026)
Most lake-carbonate-isotope records from the Maya Lowlands are based on picking fossil carbonate ostracods and gastropods, often using the species Pyrgophorus coronatus, and then combining individual specimens from a single core layer to provide a composite sample. What has been left relatively unexplored is the variability between individual shells and the impact this might have on the values obtained from such composite samples. Here, the stable carbon and oxygen isotope signatures of modern P. coronatus, a littoral and detritivore species, and other Hydrobiidae taxa ( Aroapyrgus sp. and Tryonia sp.) found in Lake Esmeralda and its much larger sister lake Chichancanab, in the Northern Maya Lowlands (also called Mayab or Yucatan Peninsula), were analysed to explore some of the environmental variables that might affect isotope composition. In addition, the carbon and oxygen isotope values derived from individual downcore gastropod shells were compared with those from bulk fine-fraction carbonate sediment from a core from Lake Esmeralda covering the last c. 6600 years. The results show that the median oxygen isotope value of a set of shells collected for a single stratigraphic layer tends to be about the same as the bulk sediment, even though their individual values can present a bimodal distribution, which might represent changes between dry and rainy seasons across the sample’s period. In addition, no significant difference in the oxygen isotope values was found in using a particular Hydrobiidae taxon over another, indicating a lack of significant vital effects. The carbon isotopic signature of modern shells varies with location within the lake, and shows relatively little variability down core, suggesting non-climatic factors may be more dominant in controlling shell carbonate δ 13 C values in these systems.

Tailored surface sulfur modification of nano-scale zero-valent iron reduces microbial toxicity and enhances compatibility with organohalide-respiring bacteria for chlorinated solvent detoxification - Feilong Gao; Jinting Liu; Han Wu; Wenzhu Zhang; Matthew J. Rogers; Jingchun Tang; Jianzhong He; Guofang Xu (Journal of Hazardous Materials, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Regional ecosystem responses to environmental drivers in cold‐water lakes evaluated using stable isotopes of salmonid fishes - Matthew R. D. Cobain; Per‐Arne Amundsen; Åge Brabrand; Pär Byström; Jan G. Davidsen; Karl Ø. Gjelland; Jennifer E. Hansen; Ingeborg P. Helland; Trygve Hesthagen; Stein I. Johnsen; Roger I. Jones; Kimmo K. Kahilainen; et al. (Limnology and Oceanography, 2026)
Diverse environmental drivers influence food web energy and nutrient flows, a key ecosystem function, yet their relative importance remains poorly known. We compiled thousands of bulk stable isotope measurements (carbon and nitrogen) of brown trout ( Salmo trutta , n = 2854) and Arctic charr ( Salvelinus alpinus , n = 3062) from 120 cold‐water lakes across northern Europe, spanning 0.02 to 1090 km 2 in size, to quantify the relative importance of nine potential drivers of energy and nutrient flows. Fish community type and individual body size matched the well‐described ecologies of the two species: charr shifted from littoral to pelagic sources with interspecific competition, and trout opportunistically increased their trophic position with piscivorous prey availability and increasing body size. The anthropogenic impacts of water‐level regulation and catchment modification were mirrored in the two species, resulting in decreased δ 13 C values, implying increased relative pelagic production in regulated lakes, and increased δ 15 N values, possibly due to increasing cross‐boundary nutrient flows. Lake size and climatic drivers (summer precipitation and winter temperature) elicited strong species‐specific changes in isotope values, suggesting that predator‐driven ecological responses can dominate over ecosystem‐wide changes in energy and nutrient flows within lake food webs. No isotopic trends were observed with catchment productivity or shoreline complexity at the regional scale, contrasting with insights from local scale studies. This spatial mismatch suggests that environmental drivers of ecosystem processes playing out at the regional scale cannot necessarily be extrapolated from localized studies, despite correlated random lake effects capturing unexplained local baseline shifts in isotopes.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Genome-enabled elucidation of nitrogen removal pathways in Thauera sp. strain SND5 - Qingkun Wang; Yifan Zhang; Chen Chen; Matthew James Rogers; Kun-Lin Yang; Jianzhong He (Water Research, 2026)

Temperature shapes the biogeography of rdhA and reductive dehalogenators in sediment across northwestern Pacific marginal seas - Yangru Xu; Yingchun Han; Xiyang Dong; Yanlei Feng; Fabai Wu; Fengmin Xing; Junyu He; Matthew J. Rogers; Xiwu Luan; Rulong Liu; Jianzhong He; Hongyue Dang; et al. (Journal of Hazardous Materials, 2026)

The palaeogeography of the Bass Strait land-bridge, a vital zone of human and biological connectivity across southeastern Australia - David M. Kennedy; Ali Jalali; Bruno David; Matthew C. McDowell; Rachel A. Nanson; Ashleigh J. Rogers; Russell Mullett; Joanna Fresløv; Jessie Birkett-Rees; Juliet Sefton; Daniel Ierodiaconou (Quaternary Science Reviews, 2025)

Tillage Management Modulates Taxonomic and Functional Structure of Soil Microbiome in Large-scale Environments - Chang Xu; Ruey Toh; Yi Zhou; Jishun Li; Roger Armstrong; Matthew D. Denton (Journal of Soil Science and Plant Nutrition, 2025)

A new theropod dinosaur lek in the Cretaceous Dakota Sandstone (Dinosaur Ridge, Colorado, USA) - Rogers C.C. Buntin; Tom Moklestad; Neffra A. Matthews; Brent Breithaupt; Paul C. Murphey; Ian Kapinos; Nora Noffke (Cretaceous Research, 2025)

Optimal placement and coordinated scheduling of distributed space-based lasers for orbital debris remediation - David O. Williams Rogers; Matthew C. Fox; Paul R. Stysley; Hang Woon Lee (Advances in Space Research, 2025)

The natural products magnetic resonance database (NP-MRD): comprehensive resource for natural products NMR data enabling discovery and understanding - John R. Cort; Jessica L. Bade; Roger G. Linington; Matthew Pin; Ella F. Poynton; Lloyd W. Sumner; James T. Koller; Zachary M. Tretter; Bharat Goel; David S. Wishart; Vasuk Gautam; Scott McKay; et al. (Phytochemistry Letters, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Hidden markov mark-recapture modeling highlights transboundary exchange for northeast pacific sablefish - Maia Kapur; Luke Rogers; Daniel R. Goethel; Matthew LH. Cheng; Dana Hanselman; Katy Echave; Melissa A. Haltuch; Kendra R. Holt; Philina English; Aaron M. Berger; Brendan Connors (Fisheries Research, 2025)

Introgression of stem rust resistance gene Sr68 from Thinopyrum junceum into wheat - Swarupa Nanda Mandal; Baljeet K. Gill; Zhixia Niu; Qijun Zhang; Daryl L. Klindworth; Santiago Bataller; Matthew N. Rouse; Yue Jin; Richard R. C. Wang; Xiwen Cai; Xiaofei Zhang; Roger Thilmony; et al. (Theoretical and Applied Genetics, 2025)

Autotrophic denitrification under anoxic conditions by newly discovered mixotrophic sulfide-oxidizing bacterium - Yifan Zhang; Qingkun Wang; Matthew J. Rogers; Jianzhong He (Bioresource Technology, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Nothing about us without us: harnessing local voices in shaping community-based adaptation in the Pacific - Hannah Turner; Briony Rogers; Sarah Kneebone; Diego Ramirez; Matthew French; Mere Jane Sawailau; Filise Volavola; Sholyn Baran; Kelera Matavesi; Orlando Newton; Maraia Batiota Luveniyali; Autiko Tela; et al. (Sustainability Science, 2025)
As global temperatures rise, so does the frequency and intensity of severe weather events and their risks to people and assets. These risks are especially acute for Pacific Islanders in urban informal settlements, given their socio-economic vulnerabilities and limited political influence. There is growing awareness that national adaptation strategies may not fully meet the needs of these vulnerable communities, leading to a focus on community-led adaptation. However, these approaches are in their infancy and have been criticised for fostering paternalistic tendencies, prompting calls for external institutions to facilitate rather than direct community initiatives. This research utilises Photovoice, a method recognised for its cultural relevance and ability to amplify Indigenous and marginalised voices. It involves 42 households in Fiji's Greater Suva Urban Area, using resident-led photography and interviews to explore community-based flood adaptation. Through ethnographic content analysis and inductive coding, the study captures residents’ experiences and strategies, identifying over 31 unique adaptation measures and underscoring the importance of resources, social networks, traditional knowledge, beliefs, and leadership in enhancing adaptive capacity. The findings demonstrate the complexity of factors influencing adaptation, with resource availability and social capital being crucial. The study advocates for adaptive processes that are community driven, calling for a shift in research and funding to support these programmes in a flexible, responsive, and inclusive manner. It also highlights the need to understand community dynamics to prevent paternalistic practices and integrate local insights effectively, ensuring community self-determination in adaptation efforts.

Diamond Gymnura natalensis and duckbill Aetomylaeus bovinus rays undertake nationwide coastal migrations - Chantel Elston; Taryn S. Murray; Toby Rogers; Matthew C. Parkinson; Bruce Q. Mann; Ryan Daly; John D. Filmalter; Paul D. Cowley (Journal of Fish Biology, 2025)
Migration is a critical aspect of ocean ecosystems, and understanding this phenomenon answers ecological and management questions. Given the difficulty in tracking ocean animals across large distances, the extent to which different ray species perform long‐distance movements, such as migrations, remains unknown. This study used passive acoustic telemetry to track the movements of endemic diamond Gymnura natalensis and critically endangered duckbill Aetomylaeus bovinus rays along the South African coastline using a collaborative nationwide network of coastal acoustic receivers for up to 7 years. Duckbill rays were detected significantly more frequently than diamond rays, but both species moved between the south and east coasts of South Africa (traveling up to 1167 km). Tagged individuals were detected significantly more often in their tagging locations during summer months but traveled significantly further distances during winter months. Furthermore, movement models fitted to individual duckbill rays' annual net‐squared displacement identified most individual annual movements as migratory. This evidence suggests that both diamond and duckbill rays make eastward winter migrations and return to specific areas along the coastline during the summer months. The exceptions to this were diamond rays tagged on the east coast that were not found to migrate seasonally, which supports previous research that there is intraspecific variability in migrations for ray species. These findings have implications for understanding ray migration not only on a global scale but also locally for spatial management interventions and population delineation.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Pollen and microplastics in hedgehog ( Erinaceus europeaus ) faeces as a means to identify landscape use in urban and sub-urban environments of the United Kingdom - Kerry Webber; Jessica McCoy; Abbie Rogers; Miranda T. Prendergast-Miller; Tamma Carel; Matthew J. Pound (Palynology, 2025)

Managing for adaptive capacity in climate-ready fisheries - Matthew N. Reimer; Anthony Rogers; James N. Sanchirico (Marine Policy, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

An expanded phylogenomic analysis of Heterolobosea reveals the deep relationships, non-canonical genetic codes, and cryptic flagellate stages in the group - Tomáš Pánek; Alexander K. Tice; Pia Corre; Pavla Hrubá; David Žihala; Ryoma Kamikawa; Euki Yazaki; Takashi Shiratori; Keitaro Kume; Tetsuo Hashimoto; Ken-ichiro Ishida; Miluše Hradilová; et al. (Molecular Phylogenetics and Evolution, 2025)

Electronic tongue measurements as a predictor for sensory properties of vacuum-packed minced beef – A preliminary study - Matthew D. Wilson; Ian G. Hunt; Samantha M. Sawyer; Chawalit Kocharunchitt; Zeer Li; Roger A. Stanley (Meat Science, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Real-time lava flow forecasting during the 2022 Mauna Loa eruption response - David M. R. Hyman; Hannah R. Dietterich; Elisabeth Gallant; Kendra J. Lynn; Michael H. Zoeller; Matthew R. Patrick; Jim Kauahikaua; Frank Trusdell; Ken Hon; Roger P. Denlinger; N. Leon Foks; R. Lopaka Lee; et al. (Bulletin of Volcanology, 2024)
On November 27, 2022, Mauna Loa (Hawai‘i) erupted for the first time in $$\sim $$ ∼ 38 years, initially producing lava flows that covered the floor of its summit caldera, Moku‘āweoweo. Over the first 12 h following the summit eruption, four main fissures opened on Mauna Loa’s Northeast Rift Zone, with “fissure 3” quickly becoming the dominant source of lava flows. For the next 12 days, fissure 3 produced a 19-km-long lava flow to the north, crossing the Mauna Loa Weather Observatory access road and coming within 2.8 km of inundating the Daniel K. Inouye Highway (Saddle Road). Within 40 min of fissure 3 opening, inundation modeling efforts had begun. For the duration of the eruption, the computational fluid dynamics model Lava2d was run in real time, using flow front locations and other field observations to make sequential forecast improvements, eventually producing a set of models which accurately predicted the routing and arrival times of lava from fissure 3. These models were used to inform timing estimates of possible future inundation of the Saddle Road. As the eruption progressed, almost 4000 Lava2d models were made using high-performance computing resources, providing critical information on uncertainty in multi-week forecasts. To our knowledge, this was the first ever real-time physics-based ensemble lava flow modeling and forecasting effort. Here, we present a chronology of these real-time efforts, focusing on the successes and limitations of this approach.

Fisheries in flux: Bridging science and policy for climate-resilient management of US fisheries under distributional change - Jacqueline M. Vogel; Arielle Levine; Catherine Longo; Rod Fujita; Catherine L. Alves; Gemma Carroll; J. Kevin Craig; Kiley Dancy; Melissa Errend; Timothy E. Essington; Nima Farchadi; Sarah Glaser; et al. (Marine Policy, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Advancing projections of crown-of-thorns starfish to support management interventions - Christina Skinner; Yves-Marie Bozec; Samuel A. Matthews; David H. Williamson; Roger Beeden; Peter J. Mumby (Science of The Total Environment, 2024)

The green convergence: United States lakes are collectively moving toward a eutrophic state - Edna G. Fernandez-Figueroa; Stephanie R. Rogers; Matthew N. Waters; Alan E. Wilson (Harmful Algae, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The biphasic activity of autophagy and heat shock protein response in peripheral blood mononuclear cells following acute resistance exercise in resistance-trained males - Kurt A. Escobar; Trisha A. VanDusseldorp; Kelly E. Johnson; Matthew Stratton; James J. McCormick; Terence Moriarity; Karol Dokladny; Roger A. Vaughan; Chad M. Kerksick; Len Kravitz; Christine M. Mermier (European Journal of Applied Physiology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Genomic and common garden data reveal significant genetic differentiation in the endangered San Fernando Valley spineflower Chorizanthe parryi var. fernandina - Deborah L. Rogers; Loraine Kohorn Washburn; Cheryl Birker; Michelle A. Labbé; Matthew A. Campbell; Andrea D. Schreier (Conservation Genetics, 2024)
San Fernando Valley spineflower ( Chorizanthe parryi var. fernandina [S. Watson] Jeps.) (Polygonaceae) is an herbaceous annual plant, endemic to California, and until rediscovered in 1999 had been thought to be extinct for almost seven decades. Historically documented at 10 locations, it currently persists at 2, separated by approximately 27 km. State listed as endangered, a description of its genetic diversity and structure is of conservation interest. After determining a lack of variation in ploidy, we examined genetic variation from samples within both populations: a common garden study for potentially adaptive genetic variation in selected growth and phenological traits and analysis of single nucleotide polymorphisms identified through restriction-site associated DNA sequencing. Both measures indicated that this highly restricted taxon nevertheless harbors substantial levels of genetic diversity and has significant between- and within-population genetic structure. Combining approaches from population genomics and common garden studies provided more insight into the patterns and basis of genetic diversity than is typical for studies of non-model species. Although local adaptation was not specifically studied (i.e., via reciprocal transplant studies), the differences determined from these two independent lines of evidence indicate that mixing gene pools between populations is not recommended at this time. Further, with significant differences revealed among subpopulations, we caution against mixing genotypes across subpopulations for the most part, and without much more evidence that this would not pose a risk of outbreeding depression. The importance of supporting pollinator health and diversity is highlighted. With genetic diversity—particularly with an annual species—being dynamic, fluctuating with the usual processes and with contributions from the soil seedbank, we recommend periodic resampling to monitor genetic diversity and structure. Climate change is anticipated to contribute to this variability.

Isolated hyperthermic perfusions for cutaneous melanoma in-transit metastasis of the limb and uveal melanoma metastasis to the liver - Anne Huibers; Danielle K. DePalo; Matthew C. Perez; Jonathan S. Zager; Roger Olofsson Bagge (Clinical & Experimental Metastasis, 2024)
Patients with cutaneous melanoma can develop in-transit metastases (ITM), most often localized to limbs. For patients with uveal melanoma that develop metastatic disease, the overall majority develop isolated liver metastases. For these types of metastases, regional cancer therapies have evolved as effective treatments. Isolated limb perfusion (ILP), isolated limb infusion (ILI), isolated hepatic perfusion (IHP) and percutaneous hepatic perfusion (PHP) achieve a high local concentration of chemotherapy with minimal systemic exposure. This review discusses the mechanism and available literature on locoregional treatment modalities in the era of modern immunotherapy.

Oncolytic intralesional therapy for metastatic melanoma - Danielle K DePalo; Matthew C. Perez; Anne Huibers; Roger Olofsson Bagge; Jonathan S. Zager (Clinical & Experimental Metastasis, 2024)

Corrigendum: Modelling the influence of coral-reef-derived dimethylsulfide on the atmosphere of the Great Barrier Reef, Australia - Rebecca L. Jackson; Matthew T. Woodhouse; Albert J. Gabric; Roger A. Cropp; Hilton B. Swan; Elisabeth S. M. Deschaseaux; Haydn Trounce (Frontiers in Marine Science, 2024)

Incidence and severity of Phoracantha-induced decline within high-elevation eucalypt woodlands are strongly associated with elevation and land management - Matthew Theodore Brookhouse; Roger Farrow; Jozef Meyer; Keith McDougall; Jessica Ward-Jones; Genevieve T. Wright (Forest Ecology and Management, 2024)

The detection of a strong episignature for Chung–Jansen syndrome, partially overlapping with Börjeson–Forssman–Lehmann and White–Kernohan syndromes - Niels Vos; Sadegheh Haghshenas; Liselot van der Laan; Perle K. M. Russel; Kathleen Rooney; Michael A. Levy; Raissa Relator; Jennifer Kerkhof; Haley McConkey; Saskia M. Maas; Lisenka E. L. M. Vissers; Bert B. A. de Vries; et al. (Human Genetics, 2024)
Chung-Jansen syndrome is a neurodevelopmental disorder characterized by intellectual disability, behavioral problems, obesity and dysmorphic features. It is caused by pathogenic variants in the PHIP gene that encodes for the Pleckstrin homology domain-interacting protein, which is part of an epigenetic modifier protein complex. Therefore, we hypothesized that PHIP haploinsufficiency may impact genome-wide DNA methylation (DNAm). We assessed the DNAm profiles of affected individuals with pathogenic and likely pathogenic PHIP variants with Infinium Methylation EPIC arrays and report a specific and sensitive DNAm episignature biomarker for Chung–Jansen syndrome. In addition, we observed similarities between the methylation profile of Chung–Jansen syndrome and that of functionally related and clinically partially overlapping genetic disorders, White–Kernohan syndrome (caused by variants in DDB1 gene) and Börjeson–Forssman–Lehmann syndrome (caused by variants in PHF6 gene). Based on these observations we also proceeded to develop a common episignature biomarker for these disorders. These newly defined episignatures can be used as part of a multiclass episignature classifier for screening of affected individuals with rare disorders and interpretation of genetic variants of unknown clinical significance, and provide further insights into the common molecular pathophysiology of the clinically-related Chung–Jansen, Börjeson–Forssman–Lehmann and White–Kernohan syndromes.

Cost–benefit analysis of ecosystem modeling to support fisheries management - Matthew H. Holden; Eva E. Plagányi; Elizabeth A. Fulton; Alexander B. Campbell; Rachel Janes; Robyn A. Lovett; Montana Wickens; Matthew P. Adams; Larissa Lubiana Botelho; Catherine M. Dichmont; Philip Erm; Kate J. Helmstedt; et al. (Journal of Fish Biology, 2024)
Mathematical and statistical models underlie many of the world's most important fisheries management decisions. Since the 19th century, difficulty calibrating and fitting such models has been used to justify the selection of simple, stationary, single‐species models to aid tactical fisheries management decisions. Whereas these justifications are reasonable, it is imperative that we quantify the value of different levels of model complexity for supporting fisheries management, especially given a changing climate, where old methodologies may no longer perform as well as in the past. Here we argue that cost‐benefit analysis is an ideal lens to assess the value of model complexity in fisheries management. While some studies have reported the benefits of model complexity in fisheries, modeling costs are rarely considered. In the absence of cost data in the literature, we report, as a starting point, relative costs of single‐species stock assessment and marine ecosystem models from two Australian organizations. We found that costs varied by two orders of magnitude, and that ecosystem model costs increased with model complexity. Using these costs, we walk through a hypothetical example of cost‐benefit analysis. The demonstration is intended to catalyze the reporting of modeling costs and benefits.

Combatting multiple aromatic organohalide pollutants in sediments by bioaugmentation with a single Dehalococcoides - Guofang Xu; Hung Liang Ng; Chen Chen; Matthew J. Rogers; Jianzhong He (Water Research, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Current extent and future opportunities for living shorelines in Australia - Rebecca L. Morris; Erin Campbell-Hooper; Elissa Waters; Melanie J. Bishop; Catherine E. Lovelock; Ryan J. Lowe; Elisabeth M.A. Strain; Paul Boon; Anthony Boxshall; Nicola K. Browne; James T. Carley; Benedikt J. Fest; et al. (Science of The Total Environment, 2024)

On-orbit calibration and performance of the EMIT imaging spectrometer - David R. Thompson; Robert O. Green; Christine Bradley; Philip G. Brodrick; Natalie Mahowald; Eyal Ben Dor; Matthew Bennett; Michael Bernas; Nimrod Carmon; K. Dana Chadwick; Roger N. Clark; Red Willow Coleman; et al. (Remote Sensing of Environment, 2024)

A volatile sulfur sink aids in reconciling the sulfur isotope mass balance of closed basin lakes - Antoine Crémière; Christopher J. Tino; Maxwell E. Pommer; Xingqian Cui; Matthew Roychowdhury; Roger E. Summons; Alex Sessions; J. Fredrick Sarg; Timothy W. Lyons; Jess F. Adkins (Geochimica et Cosmochimica Acta, 2024)

An organizing framework to break down Western-centric views of knowledge in North–South research - Hannah Turner; Briony Rogers; Sarah Kneebone; Diego Ramirez; Matthew French; Mere Jane Sawailau; Filise Volavola; Sholyn Baran; Kelera Matavesi; Orlando Newton; Maraia Batiota Luveniyali; Autiko Tela; et al. (Sustainability Science, 2024)
Global challenges, such as climate change, persistent poverty, and food insecurity are complex problems. These societal, environmental, and economic challenges cross scientific disciplines, communities, and geographies, requiring interdisciplinary, North–South solutions. Nevertheless, prevailing sustainability science responses are Western-centric. Some seminal studies have attempted to understand and engage with diverse knowledge systems. These include decolonial and Indigenous methodologies, such as “Two-Eyed Seeing”, which emphasizes the importance of using both Western and Indigenous knowledge to gain a more comprehensive understanding of the world, and participatory action research, which highlights the importance of involving participants in the research process and promoting social change through collaborative effort. However, apart from in-country research collaborations with traditional Indigenous knowledge, most North–South studies overlook the role or influence of Western-centric views and therefore fail to recognize and incorporate diverse worldviews and knowledge systems. This may, in part, reflect the tendency to categorize research into disciplinary silos, but more likely is the unintentional, yet prevalent, view that Western science is “objective and neutral.” As more scholars from multiple disciplines and geographies focus on interdisciplinary North–South research, it is critical that researchers reflect on dominant research approaches and knowledge production. Studies can co-construct, reproduce, or control the forms of knowledge generated—whether intentional or unintentional. This paper presents an organizing framework to help researchers navigate, understand, and engage with diverse forms of knowledge in undertaking North–South research. The framework draws on empirical observations from the authors’ interdisciplinary research and from empirical cross-cultural literature. It comprises three contextual levels of influence, featuring guiding principles and subsequent practical actions researchers can use to navigate the complexities of knowledge co-construction in North–South research.

Effect-based monitoring of two rivers under urban and agricultural influence reveals a range of biological activities in sediment and water extracts - Frederic D.L. Leusch; Hamish Allen; Nuwan A.L. De Silva; Roger Hodson; Matthew Johnson; Peta A. Neale; Michael Stewart; Louis A. Tremblay; Taylor Wilde; Grant L. Northcott (Journal of Environmental Management, 2024)

The house of a thousand species: The untapped potential of comprehensive biodiversity censuses of urban properties - Andrew M. Rogers; Russell Q‐Y. Yong; Matthew H. Holden (Ecology, 2024)

A multi-country panel study of behaviour, perceptions and expectations during different stages of the COVID-19 pandemic - Gloria Amaris; Julián Arellana; Matthew Beck; Roger Behrens; Chiara Calastri; Stephane Hess; Fangqing Song; Hazvinei Tsitsi Tamuka Moyo; Mark Zuidgeest (Travel Behaviour and Society, 2024)

Anthropogenic activity remains the main contributor to fecal pollution in managed tropical watersheds as unraveled by PhyloChip microarray-based microbial source tracking - Siyan Zhao; Matthew J. Rogers; Yuda Liu; Gary L. Andersen; Jianzhong He (Journal of Hazardous Materials, 2024)

Vegetation and climate dynamics at the dawn of human settlement: multiproxy palaeoenvironmental evidence from the Hashilan Wetland, western Iran - Reza Safaierad; Roger Matthews; Lydie Dupont; Bernd Zolitschka; Elena Marinova; Morteza Djamali; Christoph Vogt; Ghasem Azizi; Hamid A.K. Lahijani; Wendy Matthews (Journal of Quaternary Science, 2023)
The scarcity of high‐resolution palaeoclimate records from the interior of West Asia has limited our understanding of the mechanisms of past climate change and their potential impacts on early human societies of the Eastern Fertile Crescent. Here, we present a multiproxy sedimentological, geochemical and palynological record from the Hashilan Wetland in the central Zagros Mountains, spanning the time interval from 22 to 2.2 kcal bp. Our results indicate a cold, dry climate for the last deglaciation (22 to 10 kcal bp ) with amplified aridity during the Last Glacial Maximum, Heinrich Stadial 1, the Younger Dryas and the 8.2 and 3.2 ka events. The Early Holocene (11.6 to 7.8 kcal bp ) is characterised by prolonged dry summers, frequent spring/summer dust storms and restricted oak woodlands that gradually expanded as summers shortened toward the second half of the Holocene ( bp ). We show an out‐of‐phase Holocene moisture variation between the interior of West Asia and the Indian Summer Monsoon domain and conclude that summer insolation‐driven latitudinal shifts of the Hadley cell played a key role in seasonality changes in the interior of West Asia by modulating the strength and pathway of the subtropical high‐pressure cells. Finally, we explore possible impacts of these changes on regional prehistoric human communities.

Linking knowledge and action for climate-ready fisheries: Emerging best practices across the US - Julia G. Mason; Sarah J. Weisberg; Janelle L. Morano; Richard J. Bell; Mark Fitchett; Roger B. Griffis; Elliott L. Hazen; William D. Heyman; Kirstin Holsman; Kristin M. Kleisner; Katie Westfall; Michele K. Conrad; et al. (Marine Policy, 2023)

Loss of sea ice and intermittent winds alter distributions and diet resources of young forage fish in the Chukchi sea - Esther D. Goldstein; Ryan M. McCabe; Matthew C. Rogers; Alison L. Deary; Janet T. Duffy-Anderson (Progress in Oceanography, 2023)

Boron adsorption in clay minerals: Implications for martian groundwater chemistry and boron on Mars - Matthew A. Nellessen; Patrick Gasda; Laura Crossey; Eric Peterson; Abdulmehdi Ali; Jin Zhang; Wenyi Zhou; Ming Hao; Michael Spilde; Horton Newsom; Nina Lanza; Adriana Reyes-Newell; et al. (Icarus, 2023)

Multiband 2D InSAR deformation models with error estimates from natural neighbour interpolation: Case study in the Latrobe Valley, Australia - Paul J. Johnston; Mick S. Filmer; Thomas Fuhrmann; Matthew C. Garthwaite; Alex R. Woods; Roger W. Fraser (Advances in Space Research, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Correction to: Mitochondrial volume density and evidence for its role in adaptive divergence in response to thermal tolerance in threespine stickleback - Matthew R. J. Morris; Sara J. Smith; Jonathan Rosebush; Sean M. Rogers (Journal of Comparative Physiology B, 2023)

Stable isotopes infer the diet and habitat of the enigmatic pygmy right whale (Caperea marginata) off southern Australia - Adelaide V. Dedden; Catherine M. Kemper; Gary Truong; Matthew R. McCurry; Paul D. van Ruth; Tracey L. Rogers (Frontiers in Marine Science, 2023)
In the Southern Hemisphere, baleen whales generally undertake migrations between productive feeding grounds at high latitudes and breeding grounds at lower latitudes. Pygmy right whales ( Caperea marginata ) (PRW) are the smallest and most enigmatic baleen whale, that likely forgo long-distance migrations, and instead inhabit temperate and subantarctic waters year-round. Previous research has relied on limited data from sighting and stranding records to infer the habitat use and diet of PRWs, however the absence of long-term and consistent data has left uncertainty surrounding these parameters. We utilized bulk stable isotopes of carbon (δ 13 C) and nitrogen ( δ 15 N) in baleen from Australian PRWs (n = 14) to infer their diet and habitat use. Stable isotope values from 1980–2019 were then matched to remote sensed data from known upwelling regions (where they likely feed) to examine if their dietary patterns are related to changes in food web dynamics. We found that PRWs remained in mid-latitude waters year-round and showed no evidence of feeding in Antarctic waters. Rather, their isotopic record suggests they remain between coastal waters off southern Australia and the Subtropical Convergence, feeding on krill and copepods. Additionally, there was a weak positive relationship between PRW nitrogen stable isotope values and sea surface temperature (SST) from the eastern Great Australian Bight (GAB) and Bonney Upwelling. This suggests seasonal changes in their diet is possibly correlated to oceanographic changes which drive food-web dynamics in these regions. Unlike larger species of baleen whales that migrate further to highly productive waters in the Southern Ocean to meet their energetic demands, the small PRW, who only reach 6.5m, may sustain both feeding and breeding requirements at mid-latitudes. This is the first study to analyze long-term dietary and movement patterns of the PRW, providing an important contribution to our understanding of the species.

Mechanistic and microbial ecological insights into the impacts of micro- and nano- plastics on microbial reductive dehalogenation of organohalide pollutants - Jinting Liu; Guofang Xu; Siyan Zhao; Chen Chen; Matthew J. Rogers; Jianzhong He (Journal of Hazardous Materials, 2023)

Carbon uptake in Eurasian boreal forests dominates the high‐latitude net ecosystem carbon budget - Jennifer D. Watts; Mary Farina; John S. Kimball; Luke D. Schiferl; Zhihua Liu; Kyle A. Arndt; Donatella Zona; Ashley Ballantyne; Eugénie S. Euskirchen; Frans‐Jan W. Parmentier; Manuel Helbig; Oliver Sonnentag; et al. (Global Change Biology, 2023)
Arctic‐boreal landscapes are experiencing profound warming, along with changes in ecosystem moisture status and disturbance from fire. This region is of global importance in terms of carbon feedbacks to climate, yet the sign (sink or source) and magnitude of the Arctic‐boreal carbon budget within recent years remains highly uncertain. Here, we provide new estimates of recent (2003–2015) vegetation gross primary productivity (GPP), ecosystem respiration ( R eco ), net ecosystem CO 2 exchange (NEE; R eco − GPP), and terrestrial methane (CH 4 ) emissions for the Arctic‐boreal zone using a satellite data‐driven process‐model for northern ecosystems (TCFM‐Arctic), calibrated and evaluated using measurements from >60 tower eddy covariance (EC) sites. We used TCFM‐Arctic to obtain daily 1‐km 2 flux estimates and annual carbon budgets for the pan‐Arctic‐boreal region. Across the domain, the model indicated an overall average NEE sink of −850 Tg CO 2 ‐C year −1 . Eurasian boreal zones, especially those in Siberia, contributed to a majority of the net sink. In contrast, the tundra biome was relatively carbon neutral (ranging from small sink to source). Regional CH 4 emissions from tundra and boreal wetlands (not accounting for aquatic CH 4 ) were estimated at 35 Tg CH 4 ‐C year −1 . Accounting for additional emissions from open water aquatic bodies and from fire, using available estimates from the literature, reduced the total regional NEE sink by 21% and shifted many far northern tundra landscapes, and some boreal forests, to a net carbon source. This assessment, based on in situ observations and models, improves our understanding of the high‐latitude carbon status and also indicates a continued need for integrated site‐to‐regional assessments to monitor the vulnerability of these ecosystems to climate change.

Monitoring threatened species with environmental DNA and open ecological data: Local distribution and habitat preferences of scalloped hammerhead sharks (Sphyrna lewini) - Alyssa M. Budd; Tom Schils; Madalyn K. Cooper; Mitchell B. Lyons; Matthew S. Mills; Mari E. Deinhart; Agnès Le Port; Roger Huerlimann; Jan M. Strugnell (Biological Conservation, 2023)

Multi-method biophysical analysis in discovery, identification, and in-depth characterization of surface‐active compounds - Aikaterini A. Zompra; Styliani A. Chasapi; Matthew S. Twigg; Karina Salek; Ioannis Anestopoulos; Alex Galanis; Aglaia Pappa; Tony Gutierrez; Ibrahim M. Banat; Roger Marchant; Stephen R. Euston; Mihalis I. Panayiotidis; et al. (Frontiers in Marine Science, 2022)
Synthetic surfactants are used in several industries, including manufacturing, pharmaceutical and cosmetic’s, food and feed, agriculture, petroleum and environmental remediation for their ability to adsorb to fluid and solid-water interfaces. However, their widespread use and their synthetic preparation through environmentally unfavorable processes counterbalances the value of this class of reagents. This fact has stimulated new efforts to exploit natural sources of surfactants, such as new classes of bacterial systems or manipulation of existing biological systems, that may produce, through an environmentally friendly process, new biodegradable surfactants and emulsifiers of high commercial value. A downside of microbial production of biobased chemicals such as these types of chemicals, is that their fermentation often yields crude materials consisting of several bioproducts with complex physical and chemical properties. Extraction, identification, and efficient characterization of biosurfactants from a crude mixture of biomolecules requires carefully designed, and detailed analytical processes using state-of-the-art methods. The purpose of this review article is to present the current state-of-the-art and future outlook on the various multidisciplinary biophysical methods applied in the discovery, extraction identification, and in-depth characterization of microbially-produced surface‐active compounds.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

CMIP6 projections of ocean warming and the impact on dimethylsulfide emissions from the Great Barrier Reef, Australia - Rebecca L. Jackson; Matthew T. Woodhouse; Albert J. Gabric; Roger A. Cropp (Frontiers in Marine Science, 2022)
Coral reefs are important regional sources of biogenic sulfur to the tropical marine atmosphere, through stress-induced emissions of dimethylsulfide (DMS). Recent estimates suggest that the Great Barrier Reef (GBR), Australia emits 0.02-0.05 Tg yr -1 of DMS (equivalent to 0.010-0.026 Tg yr -1 S), with potential implications for local aerosol-cloud processes. However, the impact of ocean warming on DMS emissions from coral reefs remains uncertain, complicating efforts to improve the representation of coral reefs in DMS climatologies and climate models. We investigate the influence of predicted changes in sea surface temperature (SST), photosynthetically active radiation (PAR) and wind speed on contemporary DMS emissions from the GBR using model output from the Coupled Model Intercomparison Project Phase 6 (CMIP6). A multiple linear regression is used to calculate seawater surface DMS (DMS w ) concentration in the GBR in a contemporary (2001-2020) and end-of-century (2081-2100) scenario, as simulated by CMIP6 models under a SSP2-4.5 and SSP5-8.5 Shared Socioeconomic Pathway. By the end of this century, a 1.5-3.0°C rise in annual mean SST and a 1.1-1.7 mol m -2 d -1 increase in PAR could increase DMS w concentration in the GBR by 9.2-14.5%, leading to an increase in DMS flux of 9.5-14.3%. Previous model studies have suggested that the aerosol system has a low sensitivity to relatively large changes in coral reef-derived DMS. Therefore, the predicted change in contemporary DMS emissions is unlikely to influence the regional atmosphere. Further research is needed to understand the combined effects of temperature, light, pH, salinity and ecosystem structure on DMS production in coral reefs to better predict potential changes in emissions. Nevertheless, the findings provide insight into how predicted ocean warming may affect present-day DMS emissions and the source-strength of the GBR to the atmospheric sulfur budget.

Modelling the influence of coral-reef-derived dimethylsulfide on the atmosphere of the Great Barrier Reef, Australia - Rebecca L. Jackson; Matthew T. Woodhouse; Albert J. Gabric; Roger A. Cropp; Hilton B. Swan; Elisabeth S. M. Deschaseaux; Haydn Trounce (Frontiers in Marine Science, 2022)
Marine dimethylsulfide (DMS) is an important source of natural sulfur to the atmosphere, with potential implications for the Earth’s radiative balance. Coral reefs are important regional sources of DMS, yet their contribution is not accounted for in global DMS climatologies or in model simulations. This study accounts for coral-reef-derived DMS and investigates its influence on the atmosphere of the Great Barrier Reef (GBR), Australia, using the Australian Community Climate and Earth System Simulator Atmospheric Model version 2 (ACCESS-AM2). A climatology of seawater surface DMS (DMS w ) concentration in the GBR and an estimate of direct coral-to-air DMS flux during coral exposure to air at low tide are incorporated into the model, increasing DMS emissions from the GBR region by 0.02 Tg yr -1 . Inclusion of coral-reef-derived DMS increased annual mean atmospheric DMS concentration over north-eastern Australia by 29%, contributing to an increase in gas-phase sulfate aerosol precursors of up to 18% over the GBR. The findings suggest that the GBR is an important regional source of atmospheric sulfur, with the potential to influence local-scale aerosol-cloud processes. However, no influence on sulfate aerosol mass or number concentration was detected, even with a reduction in anthropogenic sulfur dioxide emissions, indicating that DMS may not significantly influence the regional atmosphere at monthly, annual or large spatial scales. Further research is needed to improve the representation of coral-reef-derived DMS in climate models and determine its influence on local, sub-daily aerosol-cloud processes, for which observational studies suggest that DMS may play a more important role.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Fractionation of 226Ra and Ba in the Upper North Pacific Ocean - Pieter van Beek; Roger François; Makio Honda; Matthew A. Charette; Jean-Louis Reyss; Raja Ganeshram; Christophe Monnin; Susumu Honjo (Frontiers in Marine Science, 2022)
Investigations conducted during the GEOSECS program concluded that radium-226 (T 1/2 = 1602 y) and barium are tightly correlated in waters above 2500 m in the Atlantic, Pacific and Antarctic Oceans, with a fairly uniform 226 Ra/Ba ratio of 2.3 ± 0.2 dpm µmol -1 (4.6 nmol 226 Ra/mol Ba). Here, we report new 226 Ra and Ba data obtained at three different stations in the Pacific Ocean: stations K1 and K3 in the North-West Pacific and station old Hale Aloha, off Hawaii Island. The relationship between 226 Ra and Ba found at these stations is broadly consistent with that reported during the GEOSECS program. At the three investigated stations, however, we find that the 226 Ra/Ba ratios are significantly lower in the upper 500 m of the water column than at greater depths, a pattern that was overlooked during the GEOSECS program, either because of the precision of the measurements or because of the relatively low sampling resolution in the upper 500 m. Although not always apparent in individual GEOSECS profiles, this trend was noted before from the non-zero intercept of the linear regression when plotting the global data set of Ba versus 226 Ra seawater concentration and was attributed, at least in part, to the predominance of surface input from rivers for Ba versus bottom input from sediments for 226 Ra. Similarly, low 226 Ra/Ba ratios in the upper 500 m have been reported in other oceanic basins (e.g. Atlantic Ocean). Parallel to the low 226 Ra/Ba ratios in seawater, higher 226 Ra/Ba ratios were found in suspended particles collected in the upper 500 m. This suggests that fractionation between the two elements may contribute to the lower 226 Ra/Ba ratios found in the upper 500 m, with 226 Ra being preferentially removed from surface water, possibly as a result of mass fractionation during celestite formation by acantharians and/or barite precipitation, since both chemical elements have similar ionic radius and the same configuration of valence electrons. This finding has implications for dating of marine carbonates by 226 Ra, which requires a constant initial 226 Ra/Ba ratio incorporated in the shells and for using 226 Ra as an abyssal circulation and mixing tracer.

Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research - Felicia Ceban; Alexia Leber; Muhammad Youshay Jawad; Mathew Yu; Leanna M. W. Lui; Mehala Subramaniapillai; Joshua D. Di Vincenzo; Hartej Gill; Nelson B. Rodrigues; Bing Cao; Yena Lee; Kangguang Lin; et al. (Infectious Diseases, 2022)

The pacific decadal precession and its relationship to tropical pacific decadal variability in CMIP6 models - Matthew H. Rogers; Jason C. Furtado; Bruce T. Anderson (Climate Dynamics, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Epigenetic clock and methylation studies in vervet monkeys - Anna J. Jasinska; Amin Haghani; Joseph A. Zoller; Caesar Z. Li; Adriana Arneson; Jason Ernst; Kylie Kavanagh; Matthew J. Jorgensen; Julie A. Mattison; Kevin Wojta; Oi-Wa Choi; Joseph DeYoung; et al. (GeroScience, 2022)
DNA methylation-based biomarkers of aging have been developed for many mammals but not yet for the vervet monkey ( Chlorocebus sabaeus ), which is a valuable non-human primate model for biomedical studies. We generated novel DNA methylation data from vervet cerebral cortex, blood, and liver using highly conserved mammalian CpGs represented on a custom array (HorvathMammalMethylChip40). We present six DNA methylation-based estimators of age: vervet multi-tissue epigenetic clock and tissue-specific clocks for brain cortex, blood, and liver. In addition, we developed two dual species clocks (human-vervet clocks) for measuring chronological age and relative age, respectively. Relative age was defined as ratio of chronological age to maximum lifespan to address the species differences in maximum lifespan. The high accuracy of the human-vervet clocks demonstrates that epigenetic aging processes are evolutionary conserved in primates. When applying these vervet clocks to tissue samples from another primate species, rhesus macaque, we observed high age correlations but strong offsets. We characterized CpGs that correlate significantly with age in the vervet. CpG probes that gain methylation with age across tissues were located near the targets of Polycomb proteins SUZ12 and EED and genes possessing the trimethylated H3K27 mark in their promoters. The epigenetic clocks are expected to be useful for anti-aging studies in vervets.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Body Mass Changes and Markers of Fitness, Health, and Well-Being over the First Semester of University in New Zealand Students - Matthew W. Driller; Timothy Rogers; Kim Hébert-Losier; C. Martyn Beaven (Journal of Science in Sport and Exercise, 2021)

Trade‐offs between reducing complex terminology and producing accurate interpretations from environmental DNA: Comment on “Environmental DNA: What's behind the term?” by Pawlowski et al., (2020) - Naiara Rodriguez‐Ezpeleta; Olivier Morissette; Colin W. Bean; Shivakumara Manu; Pritam Banerjee; Anaïs Lacoursière‐Roussel; Kingsly C. Beng; S. Elizabeth Alter; Fabian Roger; Luke E. Holman; Kathryn A. Stewart; Michael T. Monaghan; et al. (Molecular Ecology, 2021)
In a recent paper, “Environmental DNA: What's behind the term? Clarifying the terminology and recommendations for its future use in biomonitoring,” Pawlowski et al . argue that the term eDNA should be used to refer to the pool of DNA isolated from environmental samples, as opposed to only extra‐organismal DNA from macro‐organisms. We agree with this view. However, we are concerned that their proposed two‐level terminology specifying sampling environment and targeted taxa is overly simplistic and might hinder rather than improve clear communication about environmental DNA and its use in biomonitoring. This terminology is based on categories that are often difficult to assign and uninformative, and it overlooks a fundamental distinction within eDNA: the type of DNA (organismal or extra‐organismal) from which ecological interpretations are derived.

Freshwater input and ocean connectivity affect habitats and trophic ecology of fishes in Arctic coastal lagoons - Kevin M. Fraley; Martin D. Robards; Matthew C. Rogers; Johanna Vollenweider; Beatrice Smith; Alex Whiting; Tahzay Jones (Polar Biology, 2021)

Mitochondrial volume density and evidence for its role in adaptive divergence in response to thermal tolerance in threespine stickleback - Matthew R. J. Morris; Sara J. Smith; Jonathan Rosebush; Sean M. Rogers (Journal of Comparative Physiology B, 2021)

Pollock and “the Blob”: Impacts of a marine heatwave on walleye pollock early life stages - Lauren A. Rogers; Matthew T. Wilson; Janet T. Duffy‐Anderson; David G. Kimmel; Jesse F. Lamb (Fisheries Oceanography, 2021)
The North Pacific marine heatwave of 2014–2016 (nicknamed “The Blob”) impacted marine ecosystems from California to Alaska, USA, with cascading effects on fisheries and fishing communities. We investigated the effects of this anomalous ocean warming on early life stages of walleye pollock ( Gadus chalcogrammus ) in the Gulf of Alaska. In spring of 2015, pollock larvae were caught at record low levels relative to a 30‐year time series. Survival rates were low during the summer, and by late summer, numbers were further reduced, with very low abundances of juvenile (age‐0) pollock. Our analyses suggested multiple mechanisms for this decline: (a) Low‐saline conditions may have impacted egg buoyancy and survival; (b) population densities of zooplankton nauplii may have been too low to support first‐feeding larvae; (c) body condition of age‐0 pollock was poor and a bioenergetics model indicated that reduced quality of zooplankton prey, coupled with warmer temperatures, increased the ration required for positive growth by up to 19%, at a time when prey abundance was likely reduced. Thus, walleye pollock experienced a cascade of poor conditions for growth and survival through early life stages, resulting in the near disappearance of the 2015 year class in the population by the end of their first year. These impacts differ from previous warm years and emphasize the importance of looking beyond simple temperature–abundance relationships when predicting species responses to climate warming.

Anaerobic biodegradation of phenanthrene by a newly isolated nitrate‐dependent Achromobacter denitrificans strain PheN1 and exploration of the biotransformation processes by metabolite and genome analyses - Zuotao Zhang; Jiao Sun; Haijiao Guo; Chongyang Wang; Tingting Fang; Matthew J. Rogers; Jianzhong He; Hui Wang (Environmental Microbiology, 2021)
Summary Polycyclic aromatic hydrocarbons (PAHs) are widespread and harmful contaminants and are more persistent under anaerobic conditions. The bioremediation of PAHs in anaerobic zones has been enhanced by treating the contamination with nitrate, which is thermodynamically favourable, cost‐effective, and highly soluble. However, anaerobic PAHs biotransformation processes that employ nitrate as an electron acceptor have not been fully explored. In this study, we investigated the anaerobic biotransformation of PAHs by strain PheN1, a newly isolated phenanthrene‐degrading denitrifier, using phenanthrene as a model compound. PheN1 is phylogenetically closely related to Achromobacter denitrificans and reduces nitrate to nitrite (not N 2 ) during the anaerobic phenanthrene degradation process. Phenanthrene biotransformation processes were detected using gas chromatography–mass spectrometry and were further examined by reverse transcription‐quantitative PCR and genome analyses. Carboxylation and methylation were both found to be the initial steps in the phenanthrene degradation process. Downstream biotransformation processed benzene compounds and cyclohexane derivatives. This study describes the isolation of an anaerobic phenanthrene‐degrading bacterium along with the pure‐culture evidence of phenanthrene biotransformation processes with nitrate as an electron acceptor. The findings in this study can improve our understanding of anaerobic PAHs biodegradation processes and guide PAHs bioremediation by adding nitrate to anaerobic environments.

Using a biophysical model to investigate connectivity between spawning grounds and nursery areas of King George whiting ( Sillaginodes punctatus : Perciformes) in South Australia’s gulfs - Troy A. Rogers; Ana Redondo Rodriguez; Anthony J. Fowler; Mark J. Doubell; Michael J. Drew; Michael A. Steer; Damian Matthews; Charles James; Bronwyn M. Gillanders (Fisheries Oceanography, 2021)
Many demersal marine fish species depend on a dispersive larval stage that connects geographically discrete sub‐populations. Understanding connectivity between these sub‐populations is necessary to determine stock structure, which identifies the appropriate spatial scale for fishery management. Such connectivity is poorly understood for King George whiting ( Sillaginodes punctatus ; Perciformes) in South Australia's gulf system, even though spawning grounds and nursery areas are adequately defined. In response to declines in commercial catches and estimated biomass, this study aimed to determine the most important spawning grounds and nursery areas to recruitment, and the connectivity between them. A biophysical model was seeded with particles according to the distribution and density of eggs throughout the spawning area in 2017 and 2018. Despite inter‐annual differences in the origins of particles, dispersal pathways and predicted settlement areas remained consistent between years. Predicted settlement was generally highest to nursery areas only short distances from regional spawning grounds, consistent with previous hydrodynamic models. However, the model also predicted that spawning in one region could contribute to recruitment in an adjacent region later in the spawning season, which aligned with the breakdown of thermohaline fronts at the entrance of each gulf. The connectivity between spawning grounds and nursery areas predicted by the model is supported by spatio‐temporal patterns in the otolith chemistry of pre‐flexion larvae and settled juveniles. Consequently, the most parsimonious explanation is that the populations of King George whiting in South Australia's gulf system constitute a single, panmictic stock, which has implications for fishery management.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Multivariate Modelling of the Trace Element Chemistry of Arsenopyrite from Gold Deposits Using Higher-Dimensional Algebras - Sudharsan Thiruvengadam; Matthew Edmund Murphy; Jei Shian Tan; Roger John Watling; James Ian Stewart; Karol Miller (Mathematical Geosciences, 2020)

Splitting hairs: dietary niche breadth modelling using stable isotope analysis of a sequentially grown tissue - Matthew C. Rogers; Grant V. Hilderbrand; David D. Gustine; Kyle Joly; William B. Leacock; Buck A. Mangipane; Jeffrey M. Welker (Isotopes in Environmental and Health Studies, 2020)

A probabilistic seismic hazard assessment for Wylfa Newydd, a new nuclear site in the United Kingdom - Manuela Villani; Zygmunt Lubkowski; Matthew Free; Roger M. W. Musson; Barbara Polidoro; Rory McCully; Areti Koskosidi; Crispin Oakman; Tim Courtney; Martin Walsh (Bulletin of Earthquake Engineering, 2020)

Rural–urban disparities in colorectal cancer survival and risk among men in Utah: a statewide population-based study - Charles R. Rogers; Brenna E. Blackburn; Matthew Huntington; Karen Curtin; Roland J. Thorpe; Kerry Rowe; John Snyder; Vikrant Deshmukh; Michael Newman; Alison Fraser; Ken Smith; Mia Hashibe (Cancer Causes & Control, 2020)

Dietary Ecology of the Nigeria–Cameroon Chimpanzee (Pan troglodytes ellioti) - Ekwoge E. Abwe; Bethan J. Morgan; Roger Doudja; Fabrice Kentatchime; Flaubert Mba; Alvine Dadjo; Dana M. Venditti; Matthew W. Mitchell; Bernard Fosso; Albert Mounga; Roger C. Fotso; Mary Katherine Gonder (International Journal of Primatology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

Seasonal occurrence and site fidelity of juvenile bronze whalers (Carcharhinus brachyurus) in a temperate inverse estuary - Michael Drew; Paul Rogers; Matthew Lloyd; Charlie Huveneers (Marine Biology, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

Innovative processes and technologies for modified atmosphere packaging of fresh and fresh-cut fruits and vegetables - Matthew Deas Wilson; Roger A Stanley; Alieta Eyles; Tom Ross (Critical Reviews in Food Science and Nutrition, 2019)

Comparing Biochar Application Methods for Switchgrass Yield and C Sequestration on Contrasting Marginal Lands in Pennsylvania, USA - Roger T. Koide; Binh Thanh Nguyen; R. Howard Skinner; Curtis J. Dell; Paul R. Adler; Patrick J. Drohan; Megan Licht; Monica Boyer Matthews; Rachel Nettles; Kevin Ricks; John Watkins (BioEnergy Research, 2018)

Pre-agricultural plant management in the uplands of the central Zagros: the archaeobotanical evidence from Sheikh-e Abad - Jade Whitlam; Amy Bogaard; Roger Matthews; Wendy Matthews; Yaghoub Mohammadifar; Hengameh Ilkhani; Michael Charles (Vegetation History and Archaeobotany, 2018)

Anisohydric water use behavior links growing season evaporative demand to ring-width increment in conifers from summer-dry environments - Steve L. Voelker; R. Justin DeRose; Matthew F. Bekker; Chalita Sriladda; Nisa Leksungnoen; Roger K. Kjelgren (Trees, 2018)

Novel full-length major histocompatibility complex class I allele discovery and haplotype definition in pig-tailed macaques - Matthew R. Semler; Roger W. Wiseman; Julie A. Karl; Michael E. Graham; Samantha M. Gieger; David H. O’Connor (Immunogenetics, 2018)

Plasticity in the diel vertical movement of two pelagic predators ( Prionace glauca and Alopias vulpinus ) in the southeastern Indian Ocean - Matthew Heard; Paul J. Rogers; Barry D. Bruce; Nicolas E. Humphries; Charlie Huveneers (Fisheries Oceanography, 2018)
Management and conservation of marine predator species relies on a fundamental knowledge of their movements and behaviour. Pop‐up satellite archival tags were used to investigate the vertical movement patterns of five blue sharks ( Prionace glauca ) and one thresher shark ( Alopias vulpinus ) within the southeastern Indian Ocean. Sections of similar depth distribution, identified using a split moving window analysis, were investigated in relation to the thermal structure of the water column and activity rates. Minimum horizontal displacement of between 66 and 5,187 km for blue sharks and 16 km for the thresher shark were recorded over 863 tracking days. Maximum depths ranged from 540 to 807 m for blue sharks and 144 m for the thresher shark. All sharks displayed plasticity in their depth distribution, with diel vertical movements and surface‐oriented movements the two most common patterns. Diel movement of prey is the most likely explanation for diel vertical movements of thresher and blue sharks. This study has improved our understanding of the vertical movement patterns of these pelagic predators and the relationship between their depth distribution, temperature, and activity.

Salt tolerance of two perennial grass Brachypodium sylvaticum accessions - Nir Sade; Maria del Mar Rubio Wilhelmi; Xiaojuan Ke; Yariv Brotman; Matthew Wright; Imran Khan; Wagner De Souza; Elias Bassil; Christian M. Tobias; Roger Thilmony; John P. Vogel; Eduardo Blumwald (Plant Molecular Biology, 2018)

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

Using scale and feather traits for module construction provides a functional approach to chicken epidermal development - Weier Bao; Matthew J. Greenwold; Roger H. Sawyer (Functional & Integrative Genomics, 2017)

Loss of the ssrA genome island led to partial debromination in the PBDE respiring Dehalococcoides mccartyi strain GY50 - Chang Ding; Matthew J. Rogers; Kun‐Lin Yang; Jianzhong He (Environmental Microbiology, 2017)
Summary Polybrominated diphenyl ethers (PBDEs), chemicals commonly used as flame‐retardants in consumer products, are emerging persistent organic pollutants that are ubiquitous in the environment. In this study, we report a PBDE‐respiring isolate – Dehalococcoides mccartyi strain GY50, which debrominates the most toxic tetra‐ and penta‐BDE congeners (∼1.4 µM) to diphenyl ether within 12 days with hydrogen as the electron donor. The complete genome sequence revealed 26 reductive dehalogenase homologous genes ( rdhA s), among which three genes ( pbrA1 , pbrA2 and pbrA3 ) were highly expressed during PBDE debromination. After 10 transfers of GY50 with trichloroethene or 2,4,6‐trichlorophenol as the electron acceptor instead of PBDEs, the ssrA ‐specific genome island ( ssrA ‐GI) containing pbrA1 and pbrA2 was deleted from the genome of strain GY50, leading to two variants (strain GY52 with trichloroethene, strain GY55 with 2,4,6‐trichlorophenol) with identically impaired debromination capabilities (debromination of penta‐/tetra‐BDEs ceased at di‐BDE 15). Through analysis of Illumina paired‐end sequencing data, we identified read pairs that probably came from variants that contain ssrA ‐GI deletions, indicating their possible presence in the original strain GY50 culture. The two variant strains provide real‐time examples on rapid evolution of organohalide‐respiring organisms. As PBDE‐respiring organisms, GY50‐like strains may serve as key players in detoxifying PBDEs in contaminated environments.

Statistical treatment for the wet bias in tree-ring chronologies: a case study from the Interior West, USA - Yan Sun; Matthew F. Bekker; R. Justin DeRose; Roger Kjelgren; S.-Y. Simon Wang (Environmental and Ecological Statistics, 2017)

Midpoint attractors and species richness: Modelling the interaction between environmental drivers and geometric constraints - Robert K. Colwell; Nicholas J. Gotelli; Louise A. Ashton; Jan Beck; Gunnar Brehm; Tom M. Fayle; Konrad Fiedler; Matthew L. Forister; Michael Kessler; Roger L. Kitching; Petr Klimes; Jürgen Kluge; et al. (Ecology Letters, 2016)
We introduce a novel framework for conceptualising, quantifying and unifying discordant patterns of species richness along geographical gradients. While not itself explicitly mechanistic, this approach offers a path towards understanding mechanisms. In this study, we focused on the diverse patterns of species richness on mountainsides. We conjectured that elevational range midpoints of species may be drawn towards a single midpoint attractor – a unimodal gradient of environmental favourability. The midpoint attractor interacts with geometric constraints imposed by sea level and the mountaintop to produce taxon‐specific patterns of species richness. We developed a Bayesian simulation model to estimate the location and strength of the midpoint attractor from species occurrence data sampled along mountainsides. We also constructed midpoint predictor models to test whether environmental variables could directly account for the observed patterns of species range midpoints. We challenged these models with 16 elevational data sets, comprising 4500 species of insects, vertebrates and plants. The midpoint predictor models generally failed to predict the pattern of species midpoints. In contrast, the midpoint attractor model closely reproduced empirical spatial patterns of species richness and range midpoints. Gradients of environmental favourability, subject to geometric constraints, may parsimoniously account for elevational and other patterns of species richness.

Reorganization and expansion of the nidoviral family Arteriviridae - Jens H. Kuhn; Michael Lauck; Adam L. Bailey; Alexey M. Shchetinin; Tatyana V. Vishnevskaya; Yīmíng Bào; Terry Fei Fan Ng; Matthew LeBreton; Bradley S. Schneider; Amethyst Gillis; Ubald Tamoufe; Joseph Le Doux Diffo; et al. (Archives of Virology, 2016)

Pediatric Coronal Suture Fiber Alignment and the Effect of Interdigitation on Coronal Suture Mechanical Properties - Kelly Nicole Adamski; Andre Matthew Loyd; Albert Samost; Barry Myers; Roger Nightingale; Kathleen Smith; Cameron R. ‘Dale’ Bass (Annals of Biomedical Engineering, 2015)

A new method to generate a high-resolution global distribution map of lake chlorophyll - Michael J. Sayers; Amanda G. Grimm; Robert A. Shuchman; Andrew M. Deines; David B. Bunnell; Zachary B. Raymer; Mark W. Rogers; Whitney Woelmer; David H. Bennion; Colin N. Brooks; Matthew A. Whitley; David M. Warner; et al. (International Journal of Remote Sensing, 2015)

Safety, pharmacokinetic, and positron emission tomography evaluation of serotonin and dopamine transporter occupancy following multiple-dose administration of the triple monoamine reuptake inhibitor BMS-820836 - Ming Zheng; Lieuwe Appel; Feng Luo; Roger Lane; David Burt; Robert Risinger; Gunnar Antoni; Matthew Cahir; Sanjay Keswani; Wendy Hayes; Zubin Bhagwagar (Psychopharmacology, 2015)

Opportunities for Lean Stability Strategies - Stephen T. Colgan; Robert J. Timpano; Matthew Roberts; Roger Weaver; Kevin Ryan; Kevin W. Fields; Garry Scrivens (Journal of Pharmaceutical Innovation, 2014)

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Identification and characterization of a carboxysomal γ-carbonic anhydrase from the cyanobacterium Nostoc sp. PCC 7120 - Charlotte de Araujo; Dewan Arefeen; Yohannes Tadesse; Benedict M. Long; G. Dean Price; Roger S. Rowlett; Matthew S. Kimber; George S. Espie (Photosynthesis Research, 2014)

Gene expression plasticity evolves in response to colonization of freshwater lakes in threespine stickleback - Matthew R. J. Morris; Romain Richard; Erica H. Leder; Rowan D. H. Barrett; Nadia Aubin‐Horth; Sean M. Rogers (Molecular Ecology, 2014)
Phenotypic plasticity is predicted to facilitate individual survival and/or evolve in response to novel environments. Plasticity that facilitates survival should both permit colonization and act as a buffer against further evolution, with contemporary and derived forms predicted to be similarly plastic for a suite of traits. On the other hand, given the importance of plasticity in maintaining internal homeostasis, derived populations that encounter greater environmental heterogeneity should evolve greater plasticity. We tested the evolutionary significance of phenotypic plasticity in coastal B ritish C olumbian postglacial populations of threespine stickleback ( G asterosteus aculeatus ) that evolved under greater seasonal extremes in temperature after invading freshwater lakes from the sea. Two ancestral (contemporary marine) and two derived (contemporary freshwater) populations of stickleback were raised near their thermal tolerance extremes, 7 and 22 °C. Gene expression plasticity was estimated for more than 14 000 genes. Over five thousand genes were similarly plastic in marine and freshwater stickleback, but freshwater populations exhibited significantly more genes with plastic expression than marine populations. Furthermore, several of the loci shown to exhibit gene expression plasticity have been previously implicated in the adaptive evolution of freshwater populations, including a gene involved in mitochondrial regulation ( PPARA a). Collectively, these data provide molecular evidence that highlights the importance of plasticity in colonization and adaptation to new environments.

Western Land Managers will Need all Available Tools for Adapting to Climate Change, Including Grazing: A Critique of Beschta et al. - Tony Svejcar; Chad Boyd; Kirk Davies; Matthew Madsen; Jon Bates; Roger Sheley; Clayton Marlow; David Bohnert; Mike Borman; Ricardo Mata-Gonzàlez; John Buckhouse; Tamzen Stringham; et al. (Environmental Management, 2014)

Application of thresholds of potential concern and limits of acceptable change in the condition assessment of a significant wetland - Kerrylee Rogers; Neil Saintilan; Matthew J. Colloff; Li Wen (Environmental Monitoring and Assessment, 2013)

Scaling of standard metabolic rate in estuarine crocodiles Crocodylus porosus - Roger S. Seymour; C. M. Gienger; Matthew L. Brien; Christopher R. Tracy; S. Charlie Manolis; Grahame J. W. Webb; Keith A. Christian (Journal of Comparative Physiology B, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

On the nature of temporary yield loss in maize following canola - Roger T. Koide; Matthew S. Peoples (Plant and Soil, 2012)

A temperate palaeodiversity peak in Mesozoic dinosaurs and evidence for Late Cretaceous geographical partitioning - Philip D. Mannion; Roger B. J. Benson; Paul Upchurch; Richard J. Butler; Matthew T. Carrano; Paul M. Barrett (Global Ecology and Biogeography, 2012)
Aim Modern biodiversity peaks in the tropics and declines poleward, a pattern that is potentially driven by climate. Although this latitudinal biodiversity gradient (LBG) also characterizes the marine invertebrate fossil record, distributions of ancient terrestrial faunas are poorly understood. This study utilizes data on the dinosaur fossil record to examine spatial patterns in terrestrial biodiversity throughout the Mesozoic. Location We compiled data on fossil occurrences across the globe. Methods We compiled a comprehensive dataset of Mesozoic dinosaur genera (738), including birds. Following the utilization of sampling standardization techniques to mediate for the uneven sampling of the fossil record, we constructed latitudinal patterns of biodiversity from this dataset. Results The dominant group of Mesozoic terrestrial vertebrates did not conform to the modern LBG. Instead, dinosaur diversity was highest at temperate palaeolatitudes throughout the 160 million year span of dinosaurian evolutionary history. Latitudinal diversity correlates strongly with the distribution of land area. Late Cretaceous sauropods and ornithischians exhibit disparate LBGs. Main conclusions The continuity of the palaeotemperate peak in dinosaur diversity indicates a diminished role for climate on the Mesozoic LBG; instead, dinosaur diversity may have been driven by the amount of land area among latitudinal belts. There is no evidence that the tropics acted as a cradle for dinosaur diversity. Geographical partitioning among major clades of herbivorous dinosaurs in the Late Cretaceous may result from the advanced stages of continental fragmentation and/or differing responses to increasing latitudinal climatic zonation. Our results suggest that the modern‐day LBG on land was only established 30 million years ago, following a significant post‐Eocene recalibration, potentially related to increased seasonality.

The influence of pheasant releasing and associated management on farmland hedgerows and birds in England - Roger A. H. Draycott; Andrew N. Hoodless; Matthew Cooke; Rufus B. Sage (European Journal of Wildlife Research, 2012)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Calcium storage in plants and the implications for calcium biofortification - Maclin Dayod; Stephen Donald Tyerman; Roger Allen Leigh; Matthew Gilliham (Protoplasma, 2010)

Anatomical Global Spatial Normalization - Jack L. Lancaster; Matthew D. Cykowski; David Reese McKay; Peter V. Kochunov; Peter T. Fox; William Rogers; Arthur W. Toga; Karl Zilles; Katrin Amunts; John Mazziotta (Neuroinformatics, 2010)

Recommended nomenclature for five mammalian carboxylesterase gene families: human, mouse, and rat genes and proteins - Roger S. Holmes; Matthew W. Wright; Stanley J. F. Laulederkind; Laura A. Cox; Masakiyo Hosokawa; Teruko Imai; Shun Ishibashi; Richard Lehner; Masao Miyazaki; Everett J. Perkins; Phillip M. Potter; Matthew R. Redinbo; et al. (Mammalian Genome, 2010)

Variation in carbohydrate source–sink relations of forest and treeline white spruce in southern, interior and northern Alaska - Bjartmar Sveinbjörnsson; Matthew Smith; Tumi Traustason; Roger W. Ruess; Patrick F. Sullivan (Oecologia, 2010)

Muscle activity differs with load compliance during fatiguing contractions with the knee extensor muscles - Thorsten Rudroff; Jamie N. Justice; Stephen Matthews; Rena Zuo; Roger M. Enoka (Experimental Brain Research, 2010)

Discharge of biceps brachii motor units is modulated by load compliance and forearm posture - Thorsten Rudroff; Kimberlee Jordan; Joel A. Enoka; Stephen D. Matthews; Stéphane Baudry; Roger M. Enoka (Experimental Brain Research, 2010)

A new clade of archaic large-bodied predatory dinosaurs (Theropoda: Allosauroidea) that survived to the latest Mesozoic - Roger B. J. Benson; Matthew T. Carrano; Stephen L. Brusatte (The Science of Nature, 2010)

Moisture availability influences the effect of ultraviolet‐B radiation on leaf litter decomposition - W. KOLBY SMITH; WEI GAO; HEIDI STELTZER; MATTHEW D. WALLENSTEIN; ROGER TREE (Global Change Biology, 2010)
Altered surface ultraviolet‐B (UV‐B) radiation resulting from a combination of factors that include changes in stratospheric ozone concentrations, cloud cover, and aerosol conditions may affect litter decomposition and, thus, terrestrial nutrient cycling on a global scale. Although litter decomposition rates vary across biomes, patterns of decomposition suggest that UV‐B radiation accelerates litter decay in xeric environments where precipitation is infrequent. However, under more frequent precipitation regimes where litter decay rates are characteristically high, the effect of UV‐B radiation on litter decomposition has not been fully elucidated. To evaluate this association between moisture regime and UV‐B exposure, a litter decomposition experiment was designed for aspen ( Populus tremuloides ) leaf litter, where conditions that influence both abiotic (photodegradation) and biotic (microbial) processes could be manipulated quantitatively. We found that experimentally increasing UV‐B exposure (0, 7.4, and 11.2 kJ m −2 day −1 , respectively) did not consistently increase litter decomposition rates across simulated precipitation frequencies of 4, 12, and 24 days. Instead, a UV‐B exposure of 11.2 kJ m −2 day −1 resulted in a 13% decrease in decomposition rates under the 4‐day precipitation frequency, but an increase of 80% under the 24‐day frequency. Furthermore, the same UV‐B dose increased litter decomposition rates under the 24‐day precipitation frequency by 78% even in conditions where microbial activity was suppressed. Therefore, under more xeric conditions, greater exposure to UV‐B radiation increased decomposition rates, presumably through photodegradation. In contrast, when decomposition was not moisture‐limited, greater UV‐B exposure slowed decomposition rates, most likely from the resulting inhibition of microbial activity. Ultimately, these experimental results highlight UV‐B radiation as a potential driver of decomposition, as well as indicate that both the direction and magnitude of the UV‐B effect is dependent on moisture availability, a factor that may change according to future patterns in global precipitation.

Genomic resources and microarrays for the common carp Cyprinus carpio L. - D. R. Williams; W. Li; M. A. Hughes; S. F. Gonzalez; C. Vernon; M. C. Vidal; Z. Jeney; G. Jeney; P. Dixon; B. McAndrew; R. Bartfai; L. Orban; et al. (Journal of Fish Biology, 2008)
The common carp is an important fish species satisfying ornamental, food and recreational fisheries’ needs worldwide, but in common with other cyprinid fishes, it is particularly renowned for its environmental tolerance. Investigating the mechanistic basis of growth, disease and environmental tolerance is greatly enhanced by access to a comprehensive list of gene sequences and post‐genomic technologies. The current status of genomic resources is described for this species including 40 k cDNA clone collections, their associated expressed sequence tags (ESTs) and a developing series of 13 k–26 k cDNA microarrays fabricated from amplicons. The arrays have been directed at questions of response to environmental stress (cold and hypoxia), viral and bacterial disease and ectoparasite infection. Consequently, clones from a wide range of tissues were prepared. The authors discuss how these resources were generated and their application. Evidence is presented supporting that the carp microarray may also be useful as a heterologous set of probes in studies of other fish species.

Topological Estimation Biases with Covarion Evolution - Huai-Chun Wang; Edward Susko; Matthew Spencer; Andrew J. Roger (Journal of Molecular Evolution, 2008)

Effects of Acute Nicotine Abstinence on Cue-elicited Ventral Striatum/Nucleus Accumbens Activation in Female Cigarette Smokers: A Functional Magnetic Resonance Imaging Study - Sean P. David; Marcus R. Munafò; Heidi Johansen-Berg; James MacKillop; Lawrence H. Sweet; Ronald A. Cohen; Raymond Niaura; Robert D. Rogers; Paul M. Matthews; Robert T. Walton (Brain Imaging and Behavior, 2007)

Analysing the sensitivity behaviour of two hydrology models - Chris J. Matthews; David B. Newton; Roger D. Braddock; Bofu Yu (Environmental Modeling & Assessment, 2007)

Susceptibility of imidacloprid-resistant Colorado potato beetles to non-neonicotinoid insecticides in the laboratory and field trials - Andrei Alyokhin; Galen Dively; Megan Patterson; Matthew Mahoney; David Rogers; John Wollam (American Journal of Potato Research, 2006)

The role of dissolved organic matter bioavailability in promoting phytoplankton blooms in Florida Bay - Joseph N. Boyer; Susan K. Dailey; Patrick J. Gibson; Matthew T. Rogers; Danielle Mir-Gonzalez (Hydrobiologia, 2006)

Evidence for adiabatic decompression melting in the Southern Mariana Arc from high-Mg lavas and melt inclusions - Edward J. Kohut; Robert J. Stern; Adam J. R. Kent; Roger L. Nielsen; Sherman H. Bloomer; Matthew Leybourne (Contributions to Mineralogy and Petrology, 2006)

Pelagic ecology of a northern boundary current system: effects of upwelling on the production and distribution of sardine ( Sardinops sagax ), anchovy ( Engraulis australis ) and southern bluefin tuna ( Thunnus maccoyii ) in the Great Australian Bight - TIM M. WARD; LACHLAN J. MCLEAY; WETJENS F. DIMMLICH; PAUL J. ROGERS; SAM MCCLATCHIE; ROGER MATTHEWS; JOCHEN KÄMPF; PAUL D. VAN RUTH (Fisheries Oceanography, 2006)
Shelf waters of southern Australia support the world's only northern boundary current ecosystem. Although there are some indications of intense nitrate enrichment in the eastern Great Australian Bight (GAB) arising from upwelling of the Flinders Current, the biological consequences of these processes are poorly understood. We show that productivity in the eastern GAB is low during winter, but that coastal upwelling at several locations during the austral summer–autumn results in localized increases in surface chlorophyll a concentrations and downstream enhancement of zooplankton biomass. Sardine ( Sardinops sagax ) and anchovy ( Engraulis australis ) eggs and larvae are abundant and widely distributed in shelf waters of the eastern and central GAB during summer–autumn, with high densities of sardine eggs and larvae occurring in areas with high zooplankton biomass. Egg densities and distributions support previous evidence suggesting that the spawning biomass of sardine in the waters off South Australia is an order of magnitude higher than elsewhere in southern Australia. Sardine comprised >50% of the identified prey species of juvenile southern bluefin tuna (SBT, Thunnus maccoyii ) collected during this study. Other studies have shown that the lipid content of sardine from the GAB is relatively high during summer and autumn. We suggest that juvenile SBT migrate into the eastern and central GAB during each summer–autumn to access the high densities of lipid‐rich sardines that are available in the region during the upwelling period. Levels of primary, secondary and fish production in the eastern GAB during summer–autumn are higher than those recorded in other parts of Australia, and within the lower portion of ranges observed during upwelling events in the productive eastern boundary current systems off California, Peru and southern Africa.

Saturated and Unsaturated Water Flow in Inclined Porous Media - Scott W. Weeks; Graham C. Sander; Roger D. Braddock; Chris J. Matthews (Environmental Modeling & Assessment, 2004)

Lateral Transfer and Recompartmentalization of Calvin Cycle Enzymes of Plants and Algae - Matthew Rogers; Patrick J. Keeling (Journal of Molecular Evolution, 2004)

Modelled changes in arctic tundra snow, energy and moisture fluxes due to increased shrubs - Glen E. Liston; Joseph P. Mcfadden; Matthew Sturm; Roger A. Pielke (Global Change Biology, 2002)
In arctic tundra, shrubs can significantly modify the distribution and physical characteristics of snow, influencing the exchanges of energy and moisture between terrestrial ecosystems and the atmosphere from winter into the growing season. These interactions were studied using a spatially distributed, physically based modelling system that represents key components of the land–atmosphere system. Simulations were run for 4 years, over a 4‐km 2 tundra domain located in arctic Alaska. A shrub increase was simulated by replacing the observed moist‐tundra and wet‐tundra vegetation classes with shrub‐tundra; a procedure that modified 77% of the simulation domain. The remaining 23% of the domain, primarily ridge tops, was left as the observed dry‐tundra vegetation class. The shrub enhancement increased the averaged snow depth of the domain by 14%, decreased blowing‐snow sublimation fluxes by 68%, and increased the snowcover's thermal resistance by 15%. The shrub increase also caused significant changes in snow‐depth distribution patterns; the shrub‐enhanced areas had deeper snow, and the non‐modified areas had less snow. This snow‐distribution change influenced the timing and magnitude of all surface energy‐balance components during snowmelt. The modified snow distributions also affected meltwater fluxes, leading to greater meltwater production late in the melt season. For a region with an annual snow‐free period of approximately 90 days, the snow‐covered period decreased by 11 days on the ridges and increased by 5 days in the shrub‐enhanced areas. Arctic shrub increases impact the spatial coupling of climatically important snow, energy and moisture interactions by producing changes in both shrub‐enhanced and non‐modified areas. In addition, the temporal coupling of the climate system was modified when additional moisture held within the snowcover, because of less winter sublimation, was released as snowmelt in the spring.

Host-plant mediated effects of root herbivory on insect seed predators and their parasitoids - Gregory J. Masters; T. Hefin Jones; Matthew Rogers (Oecologia, 2001)

Expression of SNMP-1 in olfactory neurons and sensilla of male and female antennae of the silkmoth Antheraea polyphemus - Matthew E. Rogers; Rudolf A. Steinbrecht; Richard G. Vogt (Cell and Tissue Research, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Blue-winged warblers (Vermivora pinus) ?recognize? dialects in type II but not type I songs - Donald E. Kroodsma; W. Roger Meservey; Alison L. Whitlock; W. Matthew VanderHaegen (Behavioral Ecology and Sociobiology, 1984)